A multi-dimensional non-uniform corrosion model for bioabsorbable metallic vascular stents. (1st September 2021) - Shi, Weiliang; Li, Hongxia; Mitchell, Kellen; Zhang, Cheng; Zhu, Tingzhun; Jin, Yifei; Zhao, Danyang
Abstract: Bioabsorbable metallic vascular stents (BMVSs) are an innovative technological advancement in the medical engineering field of vascular implants. BMVSs have great potential to revolutionize vascular intervention, but the lack of understanding of the construction material's natural corrosion within the body inhibits the use in clinical medicine. In this study, a corrosion function concept for in vivo implants was created to develop a multi-dimensional, non-uniform corrosion model with a larger goal of simulating the mechanical integrity of BMVSs. This proposed corrosion model simulates the corrosion rate and its effects on magnesium (Mg) alloy AZ31 based on continuum damage mechanics. The model was calibrated using three degradation experiments on Mg alloy specimens. These experiments focused on multi-dimensional corrosion, mass loss rate, and mechanical integrity during the corrosion process. Lastly, to verify the applicability of the proposed model, the resulting corrosion behaviors and mechanical characteristics of the BMVSs were implemented into a finite element framework to produce an overarching simulation of the BMVS's degradation in vivo . The results of the experiments and simulations revealed a proportional link between the corrosion of BMVSs and the number of exposed surfaces. A non-linear decline in mechanical integrity with increasing mass loss was also discovered through experimentation and modeling. Furthermore, the model and simulation can provide some details about changes in morphology and mechanics during BMVS corrosion. This work gives new insights into accurately modeling for BMVS degradation and can be used to optimize product development of BMVSs. Statement of significance: Bioabsorbable metallic vascular stents (BMVSs) are an innovative technological advancement in the medical engineering field of vascular implants. Despite BMVSs have great potential to revolutionize vascular intervention, the lack of understanding of the construction material's natural corrosion within the body inhibits their use in clinical medicine. In this study, a novel multi-dimensional non-uniform corrosion model was proposed to unveil the mechanisms during the in vivo degradation of bioabsorbable metallic implants, which can accurately capture the overlooked changes in morphology and mechanics during BMVS corrosion. This work provides a technical solution to enhance the modeling accuracy in BMVS degradation and can be further used to optimize the design of BMVSs in the future. Graphical abstract: Image, graphical abstract